2018
DOI: 10.1039/c8sc01427b
|View full text |Cite
|
Sign up to set email alerts
|

Silylation reactions on nanoporous gold via homolytic Si–H activation of silanes

Abstract: We report compelling evidences that dihydrosilanes are activated in a homolytic fashion on the surface of nanoporous gold (NPG), which produces hydrogen radical and silicon moieties covalently linked to the surface of the NPG. This new reactivity has led to the development of novel silylation reactions on gold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Interestingly, the involvement of the 1,3 dipole bending vibration in such reactions can actually be predicted by the SVP model, without the expensive direct dynamics calculations. In a recent study, 137 we have shown that reactant bending modes have large overlaps with the reaction coordinate at the transition state, in support of the conclusion of Houk and coworkers. In addition, the SVP model also predicts enhancement effects for several other reactant modes, which are to be confirmed.…”
Section: Implications In Larger Reactionssupporting
confidence: 88%
“…Interestingly, the involvement of the 1,3 dipole bending vibration in such reactions can actually be predicted by the SVP model, without the expensive direct dynamics calculations. In a recent study, 137 we have shown that reactant bending modes have large overlaps with the reaction coordinate at the transition state, in support of the conclusion of Houk and coworkers. In addition, the SVP model also predicts enhancement effects for several other reactant modes, which are to be confirmed.…”
Section: Implications In Larger Reactionssupporting
confidence: 88%
“…The activation of hydrosilanes by nanogold catalysts has been utilized in various other applications. Li and co-workers 49 showed that in the presence of catalytic amounts of AuNPore, a dihydrosilane (t-Bu 2 SiH 2 ) adds to the C-O bond of epoxides or oxetanes forming acyclic silyl ethers. It was proposed, based on EPR studies, that the activation of the dihydrosilane within AuNPore occurs via a homolytic path.…”
Section: Miscellaneous Transformations From the Nano Au-catalyzed Actmentioning
confidence: 99%
“…[6,7] H2 activation and hydrogen transfer reactions are key steps in these catalytic cycles. Several mechanistic studies suggested the formation of gold hydrides as reaction intermediates, both in homogeneous [8] and heterogeneous [9,10,11] processes, but details about their mode of action remain limited.…”
Section: Introductionmentioning
confidence: 99%